PENINGKATAN KREATIVITAS MOTORIK HALUS ANAK MELALUI PENERAPAN KEGIATAN FINGER PAINTING PADA KELOMPOK B TK TUNAS HARAPAN DI KECAMATAN KOTA MANNA BENGKULU SELATAN - Emilia Gustina (PAKAR Pendidikan, 2016)
The reason the research conducted was motivated by the low creativity of children, teachers rarely conducting finger painting, teachers are reluctant to prepare the media to enhance the creativity of children, and teachers use only the available media are really very simple. General research objective is to determine the increase fine motor creativity through the application of finger painting activities in group B TK Tunas Harapan in the district of Kota Manna. The research method is using classroom action research, conducted in two cycles. The results showed that: (1) the activities of finger painting theme is determined in accordance teachers can improve fine motor creativity as evidenced by the value achieved in the first cycle of 46.7% and the second cycle increased by 83.35%; (2) the activities of finger painting with children of their own creations can improve fine motor creativity as evidenced by the success of children, in the first cycle by 45% and increased in the second cycle of 81.67%; (3) The activities of finger painting with various media can improve fine motor creativity as evidenced by the success of children in the first cycle by 45% and increased in the second cycle of 81.67%. It can be concluded that the application of finger painting activities can improve fine motor creativity in group B TK Tunas Harapan Kota Manna District of South Bengkulu.